Ds. D.P.M. Huet : 'n historiese oorsig van sy dienstyd in Suid-Afrika (1854-1867) - Spies, F.J.du T. (Francois Jacobus du Toit), 1912- (University of Pretoria, 2021)
Dissertation (MA)--University of Pretoria, 1962.